Compassionate leadership for school improvement and renewal - Lasater, Kara; LaVenia, Kristina N., 1970- (Leadership for school improvement, 2024)
Compassionate Leadership for School Improvement and Renewal aims to equip educational leaders with the knowledge, skills, and learning experiences necessary to approach their work from an intentional stance of compassion. Schools serve as both sites and sources of suffering; yet compassionate leadership can facilitate healing for students, educators, and community members. The moment is right to move the field toward a compassion-centered approach to leadership. In recent years, people around the world have experienced unfathomable loss and suffering due to the COVID-19 pandemic, persistent inequities and subsequent social justice protests, war and violence, and catastrophic natural disasters. These events created perpetual anxiety, stress, fear, uncertainty, loss, and grief for millions of people--including educators. Now perhaps more than ever, people need to give and receive compassion. The purpose of the volume is to build educational leaders' capacity to demonstrate compassion, foster collective compassion within their schools and districts, establish organizational environments in which compassion is routinely given and received, and, subsequently, transform schools into sites of healing. Ultimately, through the unique contributions of each chapter, this volume offers a path toward school improvement that is both renewing and sustaining.